Pengembangan Sistem Informasi Akademik Sekolah Sepak Bola berbasis Website menggunakan Metode Waterfall (Studi Kasus: SSB Sumbersari FC) - Eko Ramadhanu Aryputra; Buce Trias Hanggara; Satrio Agung Wicaksono (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2020)
SSB Sumbersari FC is an informal school that focuses on teaching soccer for young students. SSB has several problems that can hinder daily operational activities. The problem is that the SSB often loses registration files and has not been able to realize the desire to make a report card. Based on these problems, the need to explore the need to produce a solution. The solution provided is the creation of a football academic information system. This development uses the waterfall development model. In this development model several stages will be carried out. The needs analysis phase produces 21 functional needs and 2 non-functional needs. The design phase produces a class diagram from the server and client side. The server diagram class has 14 model classes and 15 controllers, while the client diagram class has 31 classes. The implementation phase uses the vuejs and vuetifyjs framework for the client, while for the server uses the sailsjs framework with a MySQL database. In the implementation phase it produces 21 pages or interface and 61 service endpoints. The last stage is testing using blackbox testing and SUS. Blackbox testing uses the equivalence partitioning method which results in 100% of system requirements in accordance with SSB Sumbersari FC user requests. SUS testing is done to determine the level of ease of the system based on the user, where this test produces a value of 75.9375. This value means that the academic information system developed has been in accordance with user requests, is quite preferred, but still needs to be improved again.